HOW PEOPLE AND CULTURE DRIVE DIGITAL TRANSFORMATION: LESSONS FROM PUNGGUL DIGITAL VILLAGE, BALI - Ni Putu Mirna Sari; I Gusti Ayu Agung Dewi Sucitawathi Pinatih (RADJA PUBLIKA, 2025)
Digital transformation in rural governance often focuses on technology implementation, yet many initiatives fail because they neglect human and cultural factors. Punggul Village, Bali, provides a unique case where local human capital and culture are systematically leveraged to ensure a successful and sustainable digital transformation. This study aims to analyze how leadership, capacity building, cultural intermediaries, and collaboration collectively shape the adoption and institutionalization of digital services in a rural context. A qualitative case study approach was used. Data were collected through in-depth interviews with village leaders, IT staff, local system developers, and residents, complemented by participant observation and document review. Data were analyzed through data reduction, visualization, and inference following Miles & Huberman, using Rogers' Diffusion of Innovation framework as an analytical lens. The results indicate that Punggul's transformation is rooted in a deliberate socio-organizational strategy rather than simply a technology project. Visionary leadership introduced mandatory digital training and an integrity pact linked to performance; capacity building was task-specific and ongoing; cultural intermediaries (kelian) acted as mediators to maintain inclusivity; and collaboration between the village government, developers, and residents created a responsive digital ecosystem. These elements enable villages to progress from awareness to confirmation, integrating digital practices into routine governance. This study introduces the